2014
DOI: 10.3109/15412555.2014.948991
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Carbon Monoxide Diffusing Capacity is the strongest lung function predictor of decline in 12 minute-walking distance in COPD; a 5-year follow-up study

Abstract: In a 5-year longitudinal study, DLco-measurements at baseline were the most important predictors of declining exercise capacity in COPD patients. These results suggest that integration of DLco in the clinical workup provides a more comprehensive assessment in patients with COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 46 publications
2
4
0
Order By: Relevance
“…This is in fact in line with previous findings from our group in which we could demonstrate that in patients suffering from COPD, e.g. airway obstruction, DLCO is more closely linked to reduced walk distance [38]. On the other hand, DLCO/VA was revealed as the main determinant of exercise-induced desaturation, which is in line with reported interdependence between pulmonary diffusion and oxygen desaturation during exercise in patients with diffuse systemic sclerosis and interstitial lung disease [39].…”
Section: Discussionsupporting
confidence: 93%
“…This is in fact in line with previous findings from our group in which we could demonstrate that in patients suffering from COPD, e.g. airway obstruction, DLCO is more closely linked to reduced walk distance [38]. On the other hand, DLCO/VA was revealed as the main determinant of exercise-induced desaturation, which is in line with reported interdependence between pulmonary diffusion and oxygen desaturation during exercise in patients with diffuse systemic sclerosis and interstitial lung disease [39].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, DLCO (%predicted) also correlated with ISWT distance in all groups. A previous study showed similar results, and indicated that DLCO (%predicted) was a good indicator of exercise capacity measured by the ISWT [25].…”
Section: Discussionsupporting
confidence: 70%
“…Inspiratory capacity (IC) and inspiratory capacity-to-total lung capacity ratio (IC/TLC) have been shown to be useful measures of lung function, and to be strongly associated with dyspnea 21,22. In addition, the gas transport properties of the lungs, measured using the diffusing capacity of the lung for carbon monoxide (DLCO) has previously also been associated with dyspnea,23 and has been shown to be a strong predictor of longitudinal change in walking distance in COPD 24. As such, it may be descriptive of the physical condition of the COPD patient.…”
Section: Introductionmentioning
confidence: 99%